Experimental Investigation of Antibiotic Photodegradation Using a Nanocatalyst Synthesized via an Eco-Friendly Process - Rúbia Martins Bernardes Ramos; Pablo Inocêncio Monteiro; Lizandra Viana Maurat da Rocha; Oscar Oliveira Santos; Evandro Roberto Alves; Tirzhá Lins Porto Dantas (Applied Sciences)
Iron-based nanostructures mediated by plant aqueous extract were synthesized. The nanostructures were subjected to ultraviolet radiation to degrade a difficult-to-degrade compound. Various characterization techniques were performed to analyze the morphology of the nanomaterial, including scanning electron microscopy (SEM) and transmission electron microscopy (TEM), as well as crystallinity by X-ray diffraction (XRD). The chemical composition was investigated by energy dispersive X-ray spectroscopy (EDX) and structural characteristics by Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and thermogravimetric analysis (TGA). The results showed that the nanoparticles exhibited high photocatalytic efficiency, achieving 80% degradation of the pollutant. The study concludes that iron nanoparticles synthesized with plant aqueous extract are promising for the degradation of recalcitrant compounds, combining good efficiency with a cost-effective synthesis approach.